The Legacy of the Golden Horde in the European Cartography of 15th–18th Centuries (1) - I.K. Fomenko (Золотоордынское обозрение)
The article presents the development of the European cartography of Eurasia as a reflection of the gradual accumulation of geographic and ethnographic information about people and states, which history was directly connected with the formation and subsequent dissolution of Genghis Khan’s empire. The author traces the gradual increase in the information on eastern regions among western cartographers, which however consistently compared the strengthened Russian State with the “Tartar kingdoms”. The author emphasizes as well the importance of the information provided by the European maps for the study of the state structure of the Golden Horde, of the formation of the new Eurasian nations and of Russia’s relations with the Tatar states.